2020
DOI: 10.1002/advs.202001960
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antiglioblastoma Activity and BBB Permeability by Conjugation of Paclitaxel to a Cell‐Penetrative MMP‐2‐Cleavable Peptide

Abstract: In order to solve the problems of receptor promiscuity and poor blood‐brain barrier (BBB) penetration in the treatment of glioblastomas (GBM), a novel dual‐functional nanocomplex drug delivery system is developed based on the strategy of peptide‐drug conjugates. In this study, SynB3‐PVGLIG‐PTX is designed and screened out by matrix metalloproteinase‐2 (MMP‐2), to which it exhibits the best affinity. The MMP‐2‐sensitive peptide (PVGLIG) and a cell‐penetration peptide (SynB3) are combined to form a dual‐function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Internalization and Precise Intracellular Localization of Probes. To evaluate the internalization ability of the probes, human glioma cells (U87 MG cells) with high MMP-2 expression were selected 49,50 and incubated with PKP, PKP-M, and KP for different times. Obvious red fluorescence indicated that all probes could be uptaken by cells after 24 h (Figures S13−S15).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Internalization and Precise Intracellular Localization of Probes. To evaluate the internalization ability of the probes, human glioma cells (U87 MG cells) with high MMP-2 expression were selected 49,50 and incubated with PKP, PKP-M, and KP for different times. Obvious red fluorescence indicated that all probes could be uptaken by cells after 24 h (Figures S13−S15).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Controlled release systems Gliadel [11,[31][32][33] Biodegradable wafers for the combined delivery of temozolomide and carmustine [34] Biodegradable polymer implants releasing rapamycin [35] Carboxymethylcellulose biopolymer system delivering rhodamine B [36] Hydrogel based co-delivery of paclitaxel and temozolomide [37] Convection enhanced delivery Temozolomide [40] Carboplatin [41] Iron oxide nanoparticles conjugated to epidermal growth factor receptor deletion mutant III antibody (EG-FRVIIIAb)/MRI-guided [43] Nanomaterial Systems Poly(ε-caprolactone) (PCL) based nanoparticle system to deliver the natural growth modulating tripeptide GHK (glycyl-L-histidyl-L-lysine) [58] Nanobubble-based theranostic system consisting of intravenously administered iron-platinum nanoparticles loaded with doxorubicin and surface-functionalized with transferrin [60] Peptide based therapeutics Tumor targeting peptides delivering deliver the oncolytic virus VSV∆M51, in combination with gadolinium [68] Self-assembled spherical nanoparticles containing a peptide probe (Cy5.5-SAPD-99mTc) with mitochondria targeting [69] Peptide derivatives of rabies virus glycoproteins, RVG29 and RVG15-liposome, delivering anticancer chemotherapeutic docetaxel nanoparticles and paclitaxel-cholesterol [70,71] WSW (also called PhrCACET1) peptide fused to paclitaxel nanosuspensions [72] Use of polydopamine (PDA)-coated zein-curcumin nanoparticles functionalized with the peptide G23 [73] Dual peptide nanocomplex created by combining SynB3 (a cell penetration peptide) with PVGLIG (an MMP-2 sensitive peptide) and paclitaxel [77] Focused ultrasound Temozolomide [84] BCNU [85] Liposomal O6-(4-bromothenyl)guanine (O6BTG) [86] Liposome-encapsulated doxorubicin [88] Cisplatin conjugated gold nanoparticles [89] Trastzumab [90] Author…”
Section: Methods Of Drug Delivery Specific Examplesmentioning
confidence: 99%
“…A dual peptide nanocomplex created by combining SynB3 (a cell penetration peptide) with PVGLIG (an MMP-2 sensitive peptide) and paclitaxel inhibited cell migration and invasion in multiple GBM cell lines, suppressed GBM tumor growth in vivo, and increased overall survival in a mouse model of GBM [77]. The aberrant expression of matrix metalloproteinases (MMPs) has been widely reported in tumors, and the addition of an MMP-sensitive peptide increased the tumor specificity of the drug cargo in this system.…”
Section: Peptide Based Therapeuticsmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM), which is one of the most malignant, life-threatening, and aggressive tumors of the central nervous system (CNS), can put the patient to death in an average 14-month period after diagnosis with a low 5-year relative survival rate of less than 5% [22][23][24][25]. Since no effective and non-operative treatment has been suggested to date, detecting the tumor boundaries with high precision is of great importance for surgically removing the tumor cells.…”
Section: Introductionmentioning
confidence: 99%